KANDUNGAN AUKSIN (ASAM 3-INDOL ASETAT) PADA TAHAP PERKEMBANGAN BUAH KACANG TANAH (Arachis hypogaea (L.) Merr.) - Sulistiono Sulistiono; Issirep Soemardi; Aziz Purwantoro (The East Java Biological Society, 2004)
Auxin has an important role to control both of the growth and tropism of gynophore and the development of fruit and embryo of peanut (Arachis hypogaea (L). Merr.). The experiment was carried out to examine the contents of auxin during peanut development, i.e. at the time of anthesis (day 0), at day 4, 7, 10, 15, 18, 23, and 31 after anthesis, using High Performance Liquid Chromatography (HPLC) with fluorescence detector method.Between the day of anthesis to the day 31 after anthesis, the auxin contents changed according to fruit development stage. The free auxin contents in the developed fruit (entering the soil) were higher than undeveloped fruit (not entering the soil), while the bound auxin content in the developed fruit were lower than undeveloped fruit. The lowest free auxin contents was found at the time of anthesis, then increased drastically when the gynophore grew fast and in the beginning of embryo development stage (day 7). Between the day 7 to the day 15 after anthesis, the free auxin contents were decreased. In the development fruit, the free auxin contents increased when the fruit begin to grow (day 15-18), then decreased until the seed reached its full size (day 31). In the undeveloped fruit, the free auxin contents decreased at day 7 to day 31. The bound auxin contents in the developed fruit decreased until the day 18, and increased gradually until day 31. In the undeveloped fruit, the bound auxin contents decreased at day 15 and afterward.